ANTICIPATING THE INDUSTRY IN RESPONDING TO THE PUBLICATION OF ISO 45001 OF 2018 - Masjuli Masjuli; Hanifah Handayani; Suminto Suminto (Universitas Darussalam Gontor, 2017)
The purpose of this research is to find some steps model to apply the International Standardization (ISO) 45001 to anticipate organization/industry in response to the planned publication of ISO 45001 in March 2018 by the ISO. A response worth making is to provide some steps model for the application of ISO 45001. Method to be used is qualitative. The research’s result obtained from the steps model for the application of ISO 45001 is Occupational Safety and Health (K3) policy and commitment by the management team and highest ranking leader, planning, implementation, evaluation and continual improvement, for organization/industry that has implemented Occupational Health and Safety Assessment Series (OHSAS) and will migration ISO 45001 and organization/industry that has not yet implemented OHSAS 18001 but they want to implementation the ISO 45001. Conclusion: organization/industry that has a high hazard potential and bears a business relationship to business people or to international lender must from the beginning respond to the publication of ISO 45001 by providing steps model for the application of ISO 45001 that covers commitment and policy on K3, planning, implementation, evaluation and continual improvement. Key word: ISO 45001; steps model for the application of ISO 45001; industry